Rancangan Informasi Eksekutif untuk Bidang Akademik dan Kemahasiswaan di Universitas Sebelas Maret - Yusuf Priyandari; Yuniaristanto -; Utami Sri Sundari (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2011)
Information system (IS) in Sebelas Maret University (UNS), especially for academic and student affairs is not integrated and it does not fully provide information for executives. Most of executive information or reports are provided in worksheet or paper-based reports. Ideally, the executive information should be served by an executive information system (EIS) that provide real-time information in order to support decision making for the executives. This study identify and design the executives information using the Wetherbe’s Approach with structured interviews based on Business System Planning (BSP). The stages in building the executives information are identification of user groups, identification of internal and external information which is needed by executives and management report, set information access matrix, arrange EIS conceptual framework, and initiate the EIS interface. The project result shows that there are 87 internal and 14 external information which needed by the executives. The executive information spreads in 52 internal and 8 external information in academic areas, and 35 internal and 6 external information in student affairs. The project also shows that only 15% and 17% of the internal information in academic and student affairs respectively which is supported by the existing information system in UNS. In the other hand, all of the external information can not be provided by the existing information systems in UNS.